2017
DOI: 10.1111/acps.12834
|View full text |Cite
|
Sign up to set email alerts
|

Risk profiles of personality traits for suicidality among mood disorder patients and community controls

Abstract: Risk profiles of personality traits for suicidality among mood disorder patients and community controls Objective: To examine the associations between personality traits and suicidal ideation (SI) and attempt (SA) in mood disorder patients and community controls. Method: We recruited 365 bipolar, 296 major depressive disorder patients, and 315 community controls to assess their lifetime suicidality. Participants filled out self-reported personality questionnaires to collect data of personality traits, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 55 publications
2
26
1
Order By: Relevance
“…Harm avoidance was associated with suicide risk among Croatian war veterans with PTSD (Jaksic et al, ). High harm avoidance conferred prominent and independent risks of suicidal ideation and suicide attempts in patients with mood disorders (Su et al, ). Furthermore, harm avoidance was elevated among suicide attempters, relative to nonattempters, and higher harm avoidance was associated with a greater severity of suicidal behavior (Perroud et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Harm avoidance was associated with suicide risk among Croatian war veterans with PTSD (Jaksic et al, ). High harm avoidance conferred prominent and independent risks of suicidal ideation and suicide attempts in patients with mood disorders (Su et al, ). Furthermore, harm avoidance was elevated among suicide attempters, relative to nonattempters, and higher harm avoidance was associated with a greater severity of suicidal behavior (Perroud et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The TPQ consists of 44 items that are scored as true or false. Studies have found that high harm avoidance, high novelty seeking, and low reward dependence are associated with suicidal ideation and suicide attempts (Chapman, Derbidge, Cooney, Hong, & Linehan, ; Jaksic et al, ; Jylha et al, ; Perroud et al, ; Su et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, O was a negative predictor of PB, and E and A negatively correlated with PB, respectively TB. An association between N, E, and variables related to suicide desire has already been identified [ 9 , 50 ]. Additionally, a conjoint presence of higher levels of N and lower levels of E, A and C characterized individuals with psychiatric disorders [ 51 ] and more specifically SI [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in type-I bipolar disorder identified two N-facets as relevant predictors for suicide, albeit with a smaller effect than mood disturbance (25). Moreover, Su et al (26) found that high levels of N, particularly when associated to low levels of E were predictors of suicidal behavior in individuals with no history of mood disorder. In our sample, although N is significant in separating the clusters, all three of them score very high in comparison to the general population.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, Su et al. ( 26 ) found that high levels of N, particularly when associated to low levels of E were predictors of suicidal behavior in individuals with no history of mood disorder. In our sample, although N is significant in separating the clusters, all three of them score very high in comparison to the general population.…”
Section: Discussionmentioning
confidence: 99%